Maker Movement: Creative Workshops for Pedagogical Resources and Assistive Technology development (Human Factors in Design, 2023)
Maker Movement is based on groups focused on science and technology, with the purpose of offering support to the development of projects. It aims to present the Creative Workshops of Pedagogical Resources, based on the maker culture, aimed at the production of Assistive Technology - AT for the special education public. Resulted in: 32 workshops with 328 trained professionals and 2,593 accessible pedagogical resources produced. They contributed to the sharing of practices and knowledge and to the instrumentalization of the participants in the elaboration and development of AT, according to the specificities of the students for whom they are intended, promoting access, permanence, participation and learning in the educational context.
Keywords: maker movement; assistive technology; accessible pedagogical resources